Digital Dynamics: Investigating the Correlation between Social Media Addiction and Students' Relational Aggression - Syahputra, Yuda; Solihatun, Solihatun; Hafni, Merri; Miswanto, Miswanto; Asbi, Asbi; Fajri, Nurul; Putri Karisma, Sally; Prasiska Rahmat, Candra; Erwinda, Lira (Kuras Institute, 2024)
Background of the study: In the ever-evolving digital era, this study emerges to uncover potential concealed connections between social media addiction and relational aggression behaviour among university students. Aims and scope of paper: This study aims to investigate the relationship between social media addiction and relational aggression among students at Universitas Negeri Padang Methods: The research design used in this study is correlational research. The research sample consists of 526 respondents from various faculties, aged between 19 and 30 years. Data collection was conducted through two questionnaires measuring social media addiction and relational aggression behaviour. Result: The correlation analysis of the hypothesis test, utilizing the Pearson product-moment correlation test, has provided compelling evidence. The Pearson correlation coefficient, which stands at 0.682, signifies a substantial and positive relationship between the variables under scrutiny: social media addiction and relational aggressive behaviour among students at Universitas Negeri Padang. Conclusion: There is a significant relationship between social media addiction and the prevalence of relational aggressive behaviour among Universitas Negeri Padang students.